2019
DOI: 10.1049/iet-map.2018.5254
|View full text |Cite
|
Sign up to set email alerts
|

Broadband CP crossed‐stepped‐dipole antenna incorporating a cross slotted square patch

Abstract: A simple broadband circularly polarised (CP) crossed‐dipole antenna is proposed. The antenna is composed of two crossed‐strip dipoles with two stepped sections, which are connected by vacant‐quarter rings to realise CP radiation, and a parasitic cross‐slotted square patch (CSSP) consisting of a modified square‐ring patch and a cross‐slot, which surrounds the crossed dipoles. By controlling the width ratio of the two strip sections, the stepped dipole can provide proper amplitude between two orthogonal modes to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…As a preferable candidate with the advantages of compact structure, wideband CP radiation and flexible shape, different structure of crossed-dipole CP antennas have been proposed to improve the CP performance [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. A pair of vacant-quarter printed rings with inherent 90°phase difference is usually applied in the design of wideband crossed-dipole CP antennas [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. For broadband radiation performance, the conventional dipole antennas have been changed by modifying the dipole shape [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a preferable candidate with the advantages of compact structure, wideband CP radiation and flexible shape, different structure of crossed-dipole CP antennas have been proposed to improve the CP performance [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. A pair of vacant-quarter printed rings with inherent 90°phase difference is usually applied in the design of wideband crossed-dipole CP antennas [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. For broadband radiation performance, the conventional dipole antennas have been changed by modifying the dipole shape [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the combination of modified dipoles and parasitic elements is also an effective method to enhance CP bandwidth. Previous studies have reported a cross‐dipole with parasitic bowtie‐patch [15], a half ellipse dipole with parasitic patch [16], a stepped‐dipole with parasitic cross‐slotted square‐patch [17], a driven crossed‐slot‐bowtie with parasitic bowtie‐elements [18], a crossed‐dipole with parasitic patches [19] and a trapezoidal‐dipole with parasitic patches are proposed [20], which can achieve 3‐dB ARBW of 58.6%, 68.6%, 59.1%, 90.9%, 66% and 63.4%, respectively. The underlying mechanism is that modified dipoles and parasitic elements can stimulate an individual CP mode, which jointly enhance the CP bandwidth (CPBW).…”
Section: Introductionmentioning
confidence: 99%
“…Third, the CPBW of cross‐dipoles could also be increased by combing modified cross‐dipole with parasitic elements. In past years, some References 17‐24 have introduced in turn a cross‐dipole antenna with parasitic bowtie‐patch (58.6%), a crossed‐dipole antenna with parasitic patches (66%), a half ellipse cross‐dipole antenna with parasitic patch (68.6%), a trapezoidal‐dipole with parasitic patches (63.4%), a stepped cross‐dipole antenna with parasitic cross‐slotted square‐patch (59.1%), a slot‐bowtie cross‐dipole antenna with bowtie‐elements (90.9%), a cross‐dipole antenna with asymmetric L‐shaped strips (55.2%) and a cross‐dipole antenna with four rotated metallic plates (106.1%). The underlying mechanism is that the CP resonance points come from modified cross‐dipoles and parasitic elements are combined to jointly widen the CPBW.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to modifying the CDA shape, loading of multiple patches, and strips as parasitic elements is another useful method of increasing the 3‐dB ARBW of the CDA. Examples of these parasitic elements are square‐plates (28.6%), 11 circular‐dipoles (41.3%), 12 asymmetric cross‐loop (53.4%), 13 dual square‐cavity ground (66.7%), 14 triangle‐patches (58.9%), 15 coupled metal pads (85.5%), 16 half‐ellipse dipole (68.6%), 17 trapezoidal‐dipole (63.4%), 18 stepped‐dipole (59.1%), 19 slot‐bowtie cross‐dipole (90.9%), 20 and asymmetrical L‐shaped dipole (55.2%) 21 . In addition, loading rotated grounded vertical elements as parasitic magnetic dipole is also an effective way for increasing the ARBW, such as vertical metallic plates (106.1%), 22 folded plates (74.7%), 23 metal supporting pole (6.8%), 24 and vertical metal planes (14.6%) 25 .…”
Section: Introductionmentioning
confidence: 99%